Home advantage revisited: Did COVID level the playing fields? - Paweł Strawiński; Michał Krawczyk (Central European Economic Journal (CEEJ), 2022)
The COVID-19 pandemic swept fans out of the stadiums, but matches continued to be played in most major football leagues. We make use of this natural experiment to investigate if home field advantage disappears when the home team is not supported by the fans. Focusing on four top European football leagues, we find such an effect in the Bundesliga only. We propose that this singularity may be related to the special role that the fan associations play in German football.
Keywords: D91; M50; L83; Z2; 330; football; home-field advantage; COVID-19; supporters; fans